Antithrombotic potential of new direct thrombin inhibitors built on the azaphenylalanine scaffold in two rat venous thrombosis models - Peternel, Luka; Stegnar, Mojca; Drevenšek, Gorazd; Budihna, Metka V.; Božič, Mojca; Zega, Anamarija; Štalc, Anton; Černe, Manica; Urleb, Uroš (Thrombosis and Haemostasis, 2005)
The antithrombotic potential of new direct thrombin inhibitors built on the azaphenylalanine scaffold (LK-732, LK-639 and LK-731) and their amidoxime prodrugs (LK-658, LK-633 and LK-730) was studied in comparison to argatroban and nadroparin in two rat models of venous thrombosis, induced either by complete stasis combined with hypercoagulability (model 1) or by partial stasis combined with vessel injury (model 2). In initial experiments LK-732 was established as the most promising antithrombotic of the LK inhibitors and as such was further tested. In model 1, intravenous bolus administration of LK-732 produced a dose-dependent inhibition of thrombus formation with an ID50 value of 1.3 mg/kg. This ID50 value was approximately four times higher than the ID50 value of argatroban (0.3 mg/kg; p=0.011). However, in model 2, LK-732 and argatroban decreased thrombus weight by 50% at similar ID50 values (3.8 mg/kg vs 3.0 mg/kg, respectively; p=0.726). The ex vivo anticoagulant effect of LK-732 was substantially weaker compared to argatroban at doses that produced comparable antithrombotic effects. After subcutaneous administration, in vivo thrombus weight reduction of LK inhibitors (10 mg/kg) ranged between 22 to 48%. However, their oral antithrombotic effect at a dose of 30 mg/kg was rather low. LK amidoxime prodrugs failed to produce a substantial antithrombotic effect after subcutaneous (10 mg/ kg) as well as after oral administration (30 mg/kg). In conclusion, thrombin inhibitors built on the azaphenylalanine scaffold represent a new group of intravenously effective antithrombotics. However, optimisation of the oral antithrombotic effect of amid-oxime prodrug LK-658 of the lead inhibitor LK-732 is required for justifying further development of these inhibitors.
Keywords: Thrombin inhibitors; venous thrombosis model; rat; azaphenylalanine scaffold; prodrug